2003
DOI: 10.1097/00003246-200301000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oligon central venous catheters on catheter colonization and catheter-related bloodstream infection

Abstract: Oligon treatment is effective in limiting the catheter colonization rate. Due to the limited amount of events, this study lacked the power to detect significant differences in terms of catheter-related bloodstream infection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 30 publications
0
36
0
2
Order By: Relevance
“…By July 2005 a further 11 trials had been published. [8][9][10][11][12][13][14][15][16][17][18] This review was commissioned to determine the clinical effectiveness and cost-effectiveness of CVCs treated with anti-infective agents (AI-CVCs).…”
Section: Introductionmentioning
confidence: 99%
“…By July 2005 a further 11 trials had been published. [8][9][10][11][12][13][14][15][16][17][18] This review was commissioned to determine the clinical effectiveness and cost-effectiveness of CVCs treated with anti-infective agents (AI-CVCs).…”
Section: Introductionmentioning
confidence: 99%
“…In prospective randomized clinical trails, the Oligon Vantex CVCs (SPC-CVCs) significantly reduced the incidence of catheter colonization (7,36). However, the study by Ranucci et al lacked the power to detect differences in rates of catheterrelated bloodstream infection (36).…”
Section: Discussionmentioning
confidence: 99%
“…In prospective randomized clinical trails, the Oligon Vantex CVCs (SPC-CVCs) significantly reduced the incidence of catheter colonization (7,36). However, the study by Ranucci et al lacked the power to detect differences in rates of catheterrelated bloodstream infection (36). Another recent prospective, randomized, controlled multicenter clinical trial showed that the Oligon Vantex CVCs failed to prevent CR-BSI and catheter colonization (24).…”
Section: Discussionmentioning
confidence: 99%
“…After one hour of interaction, all systems yielded 100% of death. Antimicrobial silver particles alone or in combination with other metals or elements, such as carbon or platinum (Ranucci et al, 2003) or copper (Mclean et al, 1993) were also used to impregnate biomaterials (Davenas et al, 2002). Thin polymeric films prepared by the LbL method assembled oppositely charged polyelectrolytes, loaded with silver nanoparticles and presented differential cytotoxicity representing a good approach to manage microbial burden in wounds without impairment of wound healing (Agarwal et al, 2010).…”
Section: B Amentioning
confidence: 99%
“…Silver has also been extensively used for the development of infection-resistant catheters. Polyurethane catheters in which carbon, silver and platinum particles are incorporated led to an electrochemically driven release of silver ions in the outer and inner vicinities of the catheter surface, demonstrating low catheter-related bloodstream infections (Ranucci et al, 2003). Silver-containing zeolite compounds received approval of Food and Drug Administration (FDA) for being used as food contact surfaces (Joerger, 2007).…”
Section: B Amentioning
confidence: 99%